Real-time PCR assays for diagnosing brucellar spondylitis using formalin-fixed paraffin-embedded tissues. Issue 9 (March 2018) - Li, Man; Zhou, Xingang; Li, Jingjing; Sun, Lei; Chen, Xiangmei; Wang, Peng
Abstract : Abstract: It is difficult to diagnose brucellar spondylitis because of its nonspecific clinical, radiological, and histological characteristics. This study aimed to determine whether real-time polymerase chain reaction (PCR) using formalin-fixed paraffin-embedded (FFPE) tissues was superior to conventional serum-based methods for diagnosing brucellar spondylitis. This retrospective study included 31 patients with brucellosis and a control group of 20 people with no history of brucellosis or exposure to Brucella spp. Samples from all patients with brucellar spondylitis were evaluated using Giemsa staining, the standard tube agglutination (STA) test, blood culture, and real-time PCR. The brucellar spondylitis was acute in 7 patients (22.6%), subacute in 15 patients (48.4%), and chronic in 9 patients (29%). Serological assays provided positive results for 25 patients (80.1%), real-time PCR provided positive results for 29 patients (93.5%), and blood cultures provided positive results for 11 patients (35.5%). The real-time PCR provided sensitivity of 93.5%, specificity of 100%, a positive predictive value of 100%, and a negative predictive value of 100%. The corresponding values for the STA test were 80.1%, 100%, 100%, and 76.9%, respectively. Real-time PCR provided better sensitivity than Giemsa staining, the STA test, and blood culture, although the difference between PCR and STA was not statistically significant ( P = .22). B melitensis was the only pathogen that was detected in patient with brucellar spondylitis using real-time PCR. These results suggest that real-time PCR provides a high sensitivity for diagnosing brucellar spondylitis. Furthermore, the real-time PCR results indicate that B melitensis was the causative pathogen in these cases.